Pengaruh Total Asset Turnover Dan Debt To Asset Ratio Terhadap Return On Asset Pada PT Jasa Marga (Persero) Tbk Periode 2012-2024 - Dimas Bayu Saputra; Sutiman Sutiman (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research is driven by the strategic role of toll road management companies in supporting national economic growth amid challenges such as project expansion, debt burdens, and economic fluctuations. The study aims to analyze the impact of Total Asset Turnover (TATO) and Debt to Asset Ratio (DAR) on Return On Asset (ROA) at PT Jasa Marga (Persero) Tbk for the period 2012–2024. The theoretical framework is grounded in financial management principles, specifically focusing on profitability, activity, and solvency ratios as defined by Kasmir. A quantitative descriptive method with an associative approach was employed. Secondary data were gathered through library research and internet research utilizing the company’s annual financial statements. Data analysis techniques included classical assumption tests and multiple linear regression analysis using SPSS 26 software. The findings indicate that, partially, TATO has no significant effect on ROA, with a significance value of 0.154 > 0.05. Conversely, DAR has a significant negative effect on ROA, with a significance value of 0.002 < 0.05. Simultaneously, TATO and DAR exert a significant influence on ROA, evidenced by an F-statistic of 9.700 and a significance level of 0.005. In conclusion, the company’s profitability is more substantially influenced by its debt structure than by the efficiency of asset utilization during the observed period.